The Long Shadow of Doctoral Candidate Status. Case Study - Poland - Krystian Szadkowski (Social Work & Society, 2014)
The aim of this article is to provide an empirical and theoretical background in support of the thesis that in contemporary Polish public higher education institutions, especially in the massified sector of teaching-oriented disciplines, one of the side effects of the growing enrolment (between 2004-2012) in doctoral programmes has been a decrease in the internal labour costs of institutions. The instrumentalization of these enrolments by public institutions has clearly had negative effect on the lives and career paths of doctoral candidates, understood here as a deprivation of their capabilities for work and for having a voice, mediated through their ambiguous "in-between" status. In the final part of the article a qualitative case study of a doctoral programme in Education, at one of the medium-size, medium-prestige universities in the North of Poland is presented and analysed. The article concludes that the status of doctoral candidates should be determined one way or the other (as workers or students) - this is a task for empirically-informed higher education policy in Poland in the years to come.